Emotional landscape of cultural diversity: A study of international students’ experiences - Rahmawati Salim; Titin Rahmiatin; Rahmat Nasrullah; Sitti Nurfaidah; Analiza B. Tanghal (Universitas Islam Negeri Palangka Raya, Indonesia, 2026)
Despite the growing trend in international student mobility, research on the emotional journeys of Indonesian students in this context remains limited. This phenomenological case study seeks to explore the emotional experiences of Indonesian students participating in the International Credit Transfer Program (ICT) under the Merdeka Belajar Kampus Merdeka (MBKM) program at the university in the Philippines. It analyzes how these students cope with emotional challenges and cultural adjustment during their five-month exchange. Data were collected through semi-structured interviews with six participants of the students of the ICT program purposively selected and then analyzed using thematic analysis. The interviews were transcribed verbatim in Indonesian and systematically coded to identify recurring emotional themes. Findings revealed various emotional transitions, ranging from initial excitement and anxiety to feelings of cultural enrichment and emotional growth by the end of the program. This study highlights the importance of emotional support and cultural integration in enhancing the experience of international students. It is recommended that host institutions implement structured support systems to promote student well-being. Further research is recommended to explore long-term emotional impacts and cross-cultural comparisons.